2013
DOI: 10.1037/a0031894
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support change in patients with early stage breast cancer and controls.

Abstract: Objective To identify variables associated with levels of and change in social support in a cohort of early-stage breast cancer patients and age-matched controls. Methods Telephone interviews measuring perceived social support and other demographic and psychosocial variables were conducted at 4–6 weeks and 6, 12, and 24 months after surgery (patients) or a normal/benign screening mammogram (controls). A latent trajectory model was used to model the intercept (starting point) and slope (changing) aspects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 50 publications
(86 reference statements)
6
68
1
9
Order By: Relevance
“…On average, participants reported having high levels of social support, comparable to previous results among African American women with breast cancer (Giedzinska et al, 2004; Thompson et al, 2013). The stability of social support over time was unexpected given previous research (Den Oudsten et al, 2010; Courtens et al, 1996; Bloom and Kessler, 1994), and especially because a recent study of early-stage breast cancer patients in this metropolitan area found that African American patients experienced steeper decline in social support over time compared to White women (Thompson et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…On average, participants reported having high levels of social support, comparable to previous results among African American women with breast cancer (Giedzinska et al, 2004; Thompson et al, 2013). The stability of social support over time was unexpected given previous research (Den Oudsten et al, 2010; Courtens et al, 1996; Bloom and Kessler, 1994), and especially because a recent study of early-stage breast cancer patients in this metropolitan area found that African American patients experienced steeper decline in social support over time compared to White women (Thompson et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…This modeling technique allows researchers to differentiate between a construct's systematic change over time (i.e., the slope) and the estimated initial level of a construct (i.e., the intercept) (Curran and Hussong, 2003). Growth curve models can handle data that are not normally distributed (Curran et al, 2010), which was observed previously for MOS-SSS scores (Thompson et al, 2013). Because the trial involved two study arms, differences between a one-group and a two-group model were examined using a series of difference tests as described by Bollen and Curran (2006, p. 171).…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations